Spatiotemporal variations and trends of air quality in major cities in Guizhou - Lu, Fu; Yuan, Yang; Hong, Fu; Hao, Liu (Frontiers in Environmental Science, 2023)
Tracking the evolution of air pollutants has a critical impact on our ability to further improve air quality, which have been extensively studied in the North China Plain (NCP), the Yangtze River Delta (YRD) and the Pearl River Delta (PRD) regions, but remain poorly characterized in Guizhou located in the east of Yunnan-Guizhou Plateau. Here, we analyzed spatiotemporal variations and trends of six criteria air pollutants, i.e., inhalable particles (PM10), fine particle (PM2.5), sulfur dioxide (SO2), carbon monoxide (CO), nitrogen dioxide (NO2) and ozone (O3), from 2016 to 2020 in the focus major cities in Guizhou, taking advantage of the extensive network data available since 2016. The annual mean concentrations of the six criteria air pollutants were substantially lower than China’s national ambient air quality standard (NAAQS-II), confirmed a significant improvement of air quality in Guizhou. The annual mean concentrations of PM10, PM2.5, SO2, CO and NO2 all decreased year by year during 2016–2020 in the focus major cities, and the highest decrease occurred in fall or winter. By contrast, O3 increased with a rate ranged from 0.85 μg·m−3 yr−1 (95% CI: 0∼1.78) to 3.71 μg·m−3 yr−1 (95% CI: 2.54∼5.13), and the highest increase occurred in spring or summer, revealing a strong impetus for reducing O3 pollution. Correlations among the six criteria air pollutants unveiled that the correlation coefficients between PM2.5 and NO2 were higher than those of between PM2.5 and SO2 in most focus major cities, mirroring a priority to control NOx to further reduce PM2.5 pollution in Guizhou. The focus of curbing O3 pollution in Guizhou should be redesigned to mitigate multiple precursors from multiple sectors, and efficient control strategies to mitigate warm seasons O3 pollution should also be implemented in cold seasons. Our results will benefit for our knowledge about current air pollution situation and police makers for future air pollution control in Guizhou.